The effect of Aureomycin® in combination with Bovetec® in a mineral mixture on steers grazing native grass - F.K. Brazle (Kansas Agricultural Experiment Station Research Reports, 2002)
Three hundred twelve mixed-breed steers (590 lb) were allotted randomly to eight native grass pastures on April 20. The pastures were grazed until July 13. The steers in four pastures received a basic mineral mix with 800 mg of Bovatec7 per lb. The other four pastures received the basic mineral mixture with Bovatec plus 1.6 lb Aureomycin 50 per 50 lb of mineral. The steers receiving the mineral with Aureomycin had greater mineral consumption (P<0.04). Including Aureomycin in the mineral increased gain by 2%; however, the response was not statistically significant.
Keywords: Cattlemen& #x27; s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Bovatec; Ionophore; Aureomycin; Antibiotic; Native grass